Optimum postharvest handling-effect of temperature on quality and shelf life of tropical fruits and vegetables. (Journal of Tropical Resources and Sustainable Science (JTRSS), 2019)
The challenge of high tropical temperature and chilling sensitive horticulture required an optimum postharvest handling to minimize the worldwide concern on the postharvest losses of tropical fruits and vegetables. To ensure the harvested produces achieves the consumer acceptability, the effect of temperature on the perishable produces along the integrated series of postharvest chain operations including harvesting, processing, storage and transportation must be crucially maintained. Even though the cooling process during the postharvest handling helps to reduce deterioration from high tropical temperature, the refrigeration storage temperature may also result in detrimental chilling injury. Quality of the produces reduced because of the development of symptoms include internal and external discoloration, abnormal fruit ripening, accelerated senescence, skin pitting, wilting, increase susceptibility to decay and loss of flavour. Optimum storage temperature for specific fruits and vegetables, temperature conditioning, intermittent warming technique, controlled atmosphere storage, chemical treatments and application of growth regulator can be applied either to retard the damaging symptoms or to increase the tolerance of the commodities towards chilling injury in order to extend fresh produces shelf life.
Keywords: Postharvest handling; tropical fruits; tropical vegetables; temperature; quality